Product Defect Reduction Using Quality Planning in Furniture Manufacturing - Putri Nawang Wulan; Akbar Adhiutama (Journal of Economics and Business UBS, 2023)
The purpose of this study is to find out the most common defect in the company production, the effect of defect to the company’s financial performance, and understand the cause of the defect to find out the proper solution to minimize the defect. This study interprets quality planning management and implements five steps of DMAIC for Six Sigma to find the root cause. Several methods were used for collecting data interviews, observation, and surveys. The study found that different group of customer has different sensitiveness towards defect, and it turns out their customers from non-corporate project is more sensitive towards defect than corporate project customer. An unprecise door, fracture, unfulfilling finishing, unsymmetric closing level, unergonomic product, unfitted with the site, untidy stitches, and last a varied pattern direction in one product are the type of defects that frequently arise. The cause of the defect is because the company has no project evaluation. They don’t have evaluation to measure and standards for their products quality, so defects keep happening. The recommendation for minimizing defects is, a control chart to track the progress, standard generate guiding principles and training methods for workers to develop an eye for detail.